2009
DOI: 10.1101/gad.1820709
|View full text |Cite
|
Sign up to set email alerts
|

Vasa promotes Drosophila germline stem cell differentiation by activating mei-P26 translation by directly interacting with a (U)-rich motif in its 3′ UTR

Abstract: Vasa (Vas) is a DEAD-box RNA-binding protein required in Drosophila at several steps of oogenesis and for primordial germ cell (PGC) specification. Vas associates with eukaryotic initiation factor 5B (eIF5B), and this interaction has been implicated in translational activation of gurken mRNA in the oocyte. Vas is expressed in all ovarian germline cells, and aspects of the vas-null phenotype suggest a function in regulating the balance between germline stem cells (GSCs) and their fate-restricted descendants. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
105
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(115 citation statements)
references
References 59 publications
4
105
0
1
Order By: Relevance
“…Mei-p26 is involved in germ cell development in Drosophila (22)(23)(24). Previous reports have shown that translation of mei-P26 mRNA is controlled by Bam, Bgcn, CCR4, Vasa, and Tut (22,(25)(26)(27). Therefore, Mei-p26 may represent a key node in the mRNA metabolism network that controls distinct developmental programs during germ cell formation and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Mei-p26 is involved in germ cell development in Drosophila (22)(23)(24). Previous reports have shown that translation of mei-P26 mRNA is controlled by Bam, Bgcn, CCR4, Vasa, and Tut (22,(25)(26)(27). Therefore, Mei-p26 may represent a key node in the mRNA metabolism network that controls distinct developmental programs during germ cell formation and maturation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the Drosophila ortholog of DDX4, Vasa, is an atypical RNA helicase because it stimulates the translation of the mei-P26 mRNA by binding a U-rich 3 0 UTR element and recruiting the initiation factor Eif5b (Liu et al 2009, Parsyan et al 2011. The sequencespecific binding of Vasa is thought to be mediated by an RNA-binding motif, RGG, which appears eight times in the w200-amino acid-long N-terminal segments of Vasa, outside of the RNA helicase domain (Liu et al 2009).…”
Section: Cpeb1: the Cytoplasmic Polyadenylation Elementbinding Proteinmentioning
confidence: 99%
“…The sequencespecific binding of Vasa is thought to be mediated by an RNA-binding motif, RGG, which appears eight times in the w200-amino acid-long N-terminal segments of Vasa, outside of the RNA helicase domain (Liu et al 2009). Four RGG motifs are present in the N-terminal segment of mouse and human DDX4, and the IUpred algorithm (http://iupred.enzim.hu) predicts that the N-terminal segments of Vasa and DDX4 are unstructured (Kleene 2013 unpublished), a feature shared by many RBPs (Castello et al 2012).…”
Section: Cpeb1: the Cytoplasmic Polyadenylation Elementbinding Proteinmentioning
confidence: 99%
“…Rabbit anti-Brat (kindly provided by G. Morata), guinea pig anti-dMyc (Herranz et al 2008), rabbit anti-Mei-P26 (Liu et al 2009), rat anti-Elav (Hybridoma Bank), and rabbit anti-bGal (Cappel) were used. Secondary antibodies were obtained from Molecular Probes.…”
Section: Immunohistochemistry and In Situ Hybridizationmentioning
confidence: 99%